Secondary production and biomass of Cladocera in marginal lakes after the recovery of their hydrologic connectivity with a tropical river - Panarelli, Eliana Aparecida; Casanova, Silvia Maria Cagliriane [UNESP]; Henry, Raoul [UNESP] (Wiley, 2010)
Secondary production and biomass of Cladoceran populations were studied in two marginal lakes whose connections to atropical river were re-established after a prolonged drought period. This study investigates the process of the recovery ofthe cladoceran populations after the hydrologic reconnection with the river was established. It also compares the ener-getic dynamic of Cladoceran populations in two lakes, one with a wide and another with a narrow connection to the river.Samples were collected every 48 h for 1 month, immediately after the river water inflow to the lakes, and 7 months afterthe reconnection with the river during a period of hydrologic stability of the lakes. Secondary production and biomasswere compared between lakes and periods, to identify the main controlling factors for the observed variations in Cladoc-eran productivity. Cladocerans were more productive during the rainy period, immediately after the increased water vol-ume, when high water temperatures were recorded in the two lacustrine systems. Secondary production and biomassvalues were higher in the more eutrophic lake, wherein the water chemical and physical characteristics presented slowalterations during the rainy period. Although the lake with large spatial heterogeneity and linkages with the river exhib-ited high Cladoceran richness, the secondary production and biomass were low. Variations in water volumes and temper-atures and changes in trophic status affected the secondary production and biomass of the main Cladoceran species inthe two studied lakes.
Keywords: Biomass; Cladocera; Marginal lakes; River–reservoir transition zone; Secondary production